Transcranial Sonography (TCS) of Brain Parenchyma in Movement Disorders: Quality Standards, Diagnostic Applications and Novel Technologies - Walter, U.; Školoudík, D. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Transcranial B-mode sonography (TCS) of brain parenchyma is being increasingly used as a diagnostic tool in movement disorders. Compared to other neuroimaging modalities such as magnetic resonance imaging (MRI) and computed tomography, TCS can be performed today with portable machines and has the advantages of noninvasiveness and high resistance to movement artifacts. In distinct brain disorders TCS detects abnormalities that cannot be visualized or can only be visualized with significant effort with other imaging methods. In the field of movement disorders, TCS has been established mainly as a tool for the early and differential diagnosis of Parkinson’s disease. The postoperative position control of deep brain stimulation electrodes, especially in the subthalamic nucleus, can reliably and safely be performed with TCS. The present update review summarizes the current methodological standards and defines quality criteria of adequate TCS imaging and assessment of diagnostically relevant deep brain structures such as substantia nigra, brainstem raphe, basal ganglia and ventricles. Finally, an overview is given on recent technological advances including TCS-MRI fusion imaging and upcoming technologies of digitized image analysis aiming at a more investigator-independent assessment of deep brain structures on TCS.
Keywords: basal ganglia; brain; ultrasound; movement disorders; TCS